Inhibition of angiogenesis and endothelial cell functions are novel sulforaphane-mediated mechanisms in chemoprevention - Bertl, Elisabeth; Bartsch, Helmut; Gerhäuser, Clarissa (Molecular cancer therapeutics, 2006)
Sulforaphane, an aliphatic isothiocyanate, is a known cancer chemopreventive agent. Aiming to investigate antiangiogenic potential of sulforaphane, we here report a potent decrease of newly formed microcapillaries in a human in vitro antiangiogenesis model, with an IC50 of 0.08 μmol/L. The effects of sulforaphane on endothelial cell functions essential for angiogenesis were investigated in HMEC-1, an immortalized human microvascular endothelial cell line. Molecular signaling pathways leading to activation of endothelial cell proliferation and degradation of the basement membrane were analyzed by reverse transcription-PCR. Sulforaphane showed time- and concentration-dependent inhibitory effects on hypoxia-induced mRNA expression of vascular endothelial growth factor and two angiogenesis-associated transcription factors, hypoxia-inducible factor-1α and c-Myc, in a concentration range of 0.8 to 25 μmol/L. In addition, the expression of the vascular endothelial growth factor receptor KDR/flk-1 was inhibited by sulforaphane at the transcriptional level. Sulforaphane could also affect basement membrane integrity, as it suppressed transcription of the predominant endothelial collagenase matrix metalloproteinase-2 and its tissue inhibitor of metalloproteinase-2. Migration of HMEC-1 cells in a wound healing assay was effectively prevented by sulforaphane at submicromolar concentrations, and we determined an IC50 of 0.69 μmol/L. In addition, within 6 hours of incubation, sulforaphane inhibited tube formation of HMEC-1 cells on basement membrane matrix at 0.1, 1, and 10 μmol/L concentrations. These effects were not due to inhibition of HMEC-1 cell proliferation; however, after 72 hours of incubation, sulforaphane nonselectively reduced HMEC-1 cell growth with an IC50 of 11.3 μmol/L. In conclusion, we have shown that sulforaphane interferes with all essential steps of neovascularization from proangiogenic signaling and basement membrane integrity to endothelial cell proliferation, migration, and tube formation. These novel antiangiogenic activities of sulforaphane are likely to contribute to its cancer chemopreventive and therapeutic potential. [Mol Cancer Ther 2006;5(3):575-85]
Gesehen am 23.11.2020